What type of information calls the attention of forecasters? Evidence from survey data in an emerging market. (December 2022) - de Mendonça, Helder Ferreira; Vereda, Luciano; Araujo, Mateus de Azevedo
Highlights: Determinants of the attention dedicated to the forecasts of macroeconomic indicators. Measures of attention based on: "active participation" and "update forecasts" Routines, incentives, risk, and information releases affect attention. Inflation is the macroeconomic indicator that attracts more attention. Abstract: This article analyzes the daily determinants of the degree of attention dedicated to the forecasts of three macroeconomic indicators: inflation, exchange rate, and output growth. Based on micro-data of expectations provided by the Central Bank of Brazil, we calculated two measures of the degree of attention: "active participation" and "update forecasts". In addition, we present various stylized facts and perform several regressions that explain the daily degree of attention dedicated to forecasts taking into account: routine and horizons, incentives, risk, and information release events. The findings show that the main aspects that can increase the attention are: routines, incentive events, and releases of direct information regarding the macroeconomic indicator under consideration. Moreover, information concerning monetary policy decisions increases the degree of attention.